Serum Antibody Binding and Cytotoxicity to Pig Cells in Chinese Subjects: Relevance to Clinical Renal Xenotransplantation - Li, Tao; Feng, Hao; Du, Jiaxiang; Xia, Qiangbing; Cooper, David K. C.; Jiang, Hongtao; He, Songzhe; Pan, Dengke; Chen, Gang; Wang, Yi (Frontiers in Immunology, 2022)
Kidney xenotransplantation is expected to contribute to resolving the shortage of kidneys from deceased human donors. Although progress in experimental life-supporting pig renal xenotransplantation has been encouraging, there are still issues to be considered before a clinical trial can be initiated. We attempted to clarify some of these by an in vitro study. Blood was drawn from healthy volunteers (Volunteers, n=20), patients with end-stage renal disease (ESRD, n=20) pre-operation (Pre), and on Day 1 (POD 1) and Day 14 (POD 14) after renal allotransplantation, brain-dead organ donors (DBD, n=20), and renal allotransplant recipients who were currently experiencing T cell-mediated rejection (Allo-TCMR, n=20). Serum IgM/IgG binding to, and complement-dependent cytotoxicity (CDC) of, PBMCs and RBCs from (a) wild-type (WT), (b) α1,3-galactosyltransferase gene-knockout (GTKO), (c) GTKO/beta-1,4-N-acety1 galactosaminyltransferase 2-knockout (GTKO/β4GalNT2KO), (d) GTKO/cytidine monophosphate-N-acetylneuraminic acid hydroxylase-knockout (GTKO/CMAHKO), and (e) GTKO/β4GalNT2KO/CMAHKO/hCD55 (TKO/hCD55) pigs were measured by flow cytometry. We obtained the following results: (i) Serum IgM/IgG binding and CDC in Volunteers were significantly greater to WT, GTKO, and GTKO/β4GalNT2KO PBMCs or RBCs than to GTKO/CMAHKO and TKO/hCD55 cells; (ii) ESRD, DBD, and Allo-TCMR serum antibody binding and CDC to WT pig PBMCs were significantly greater than to GTKO, GTKO/β4GalNT2KO, GTKO/CMAHKO, and TKO/hCD55 cells; (iii) antibody binding to GTKO/CMAHKO pig cells was significantly lower in hemodialysis than peritoneal dialysis patients. (iv) Two of twenty allotransplantation recipients’ serum IgG binding to GTKO pig PBMCs increased on POD14 compared with Pre, but IgG binding to GTKO pig RBCs did not; (v) In all sera, the lowest antibody binding and CDC were to GTKO/CMAHKO and TKO/CD55 pig cells. We conclude (i) CMAHKO in the pig may be critical to the success of clinical pig kidney xenotransplantation, and may be the most important after GTKO, at least in Chinese patients; (ii) subjects with ESRD, or who are immunosuppressed after kidney allotransplantation, and DBD, have lower levels of antibody binding and CDC to genetically-engineered pig cells than do volunteers; (iii) TKO pigs with selected human ‘protective’ transgenes, e.g., CD55, are likely to prove to be the optimal sources of kidneys for clinical xenotransplantation.